Incorporation of zinc oxide nanoparticles and it’s antibacterial effect on toothpaste - Shahawi, Amal M. El (2023)
Dental caries is the most prevalent oral infection affecting the individuals worldwide, and Streptococcus mutans is the major microorganism involved in its pathology. Thus, the aim was to evaluate the antibacterial effect of addition of nanozinc particles on toothpaste with different concentrations. The study was carried out as Deburdent toothpaste was used as a control group, and nanozinc particles were added with different concentrations to the same toothpaste, and antibacterial test for each group was evaluated.